2022
DOI: 10.31557/apjcp.2022.23.3.815
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Awareness, and Practices of University Students Toward the Role of Dietary and Lifestyle Behaviors in Colorectal Cancer: A Cross-Sectional Study from Sharjah/UAE

Abstract: Background: The incidence of colorectal cancer (CRC) has risen worldwide, with increasing prevalence in the UAE and GCC during the last few decades. Dietary and lifestyle behaviors play a pivotal role in the development and prevention of sporadic, with knowledge and awareness considered the first line of defence. Knowledge, awareness, and practices have been examined in different parts of the world, with scarce research have been conducted in the GCC countries and the UAE in particular. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
6
3
0
Order By: Relevance
“…Nonetheless, the findings of this study were consistent with those reported by Hashim et al [ 36 ]. The average knowledge and awareness of the participants about modifiable factors (73.6%) were more than nonmodifiable risk factors (40.8%).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Nonetheless, the findings of this study were consistent with those reported by Hashim et al [ 36 ]. The average knowledge and awareness of the participants about modifiable factors (73.6%) were more than nonmodifiable risk factors (40.8%).…”
Section: Discussionsupporting
confidence: 93%
“…72% responded with the correct answer, showing a good knowledge regarding obesity and CRC. This result ties in well with the findings of Hashim et al [ 36 ] and Ahmad et al [ 24 ], but lower than those reported by Saeed et al [ 18 ], Mhaidat et al [ 23 ], and Tfaily et al [ 19 ]. The prevalence of diabetes in Jordan is increasing steadily, where the overall aged-standardized prevalence increased from 14.2% in 1994 to 23.7% in 2017 [ 52 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The type of diet also showed to have a strong influence on symptom reporting. Symptoms increased in women with high caloric food intake that contains high amounts of fat, sugar, and salt, while greatly decreased with increased healthy food intake like fruit [ 41 ].…”
Section: Discussionmentioning
confidence: 99%